Ties out of bloodshed: Collective memory, cultural trauma, and the prosecution and execution of Timothy McVeigh - Madeira, Jody Lyneé (2007)
In the aftermath of the Oklahoma City bombing, processes of reconstructionremembering victims, caring for family members and survivors, and punishing the perpetrators- -began even as dcbris from the Murrah Federal Building was bcing cleared. This dissertation explores how collective memory of the bombing among family members and survivors was constructed through their participation in groups tormed after the bombing and in the legal proceedings against perpetrators Timothy McVeigh and Terry Nichols. These acts cultivated the formation of various relationships-between family members and survivors as well as between these victimized populations and the perpetrators-that both helped and hindered individual and communal reconstructions of meaning. Based upon data obtained through intensive interviews with victims' family members and survivors, this research studies the impact of membership in advocacy groups on memory work, the tensions that Timothy McVeigh's presence and actions introduced into the lives of family members and survivors, and McVeigh's execution as an event which freed memory work that had stymied in the years since the bombing. The implications of this case study illustrate in what ways concepts such as victimhood and justice are continually being expanded, with the implication that the law as a social institution is called upon to mediate cultural trauma and cultivate collective memory more consciously